Lung volumes identify an at-risk group in persons with prolonged secondhand tobacco smoke exposure but without overt airflow obstruction. Issue 1 (5th May 2018) - Arjomandi, Mehrdad; Zeng, Siyang; Geerts, Jeroen; Stiner, Rachel K; Bos, Bruce; van Koeverden, Ian; Keene, Jason; Elicker, Brett; Blanc, Paul D; Gold, Warren M
Abstract : Introduction: Exposure to secondhand smoke (SHS) is associated with occult obstructive lung disease as evident by abnormal airflow indices representing small airway disease despite having preserved spirometry (normal forced expiratory volume in 1 s-to-forced vital capacity ratio, FEV1 /FVC). The significance of lung volumes that reflect air trapping in the presence of preserved spirometry is unclear. Methods: To investigate whether lung volumes representing air trapping could determine susceptibility to respiratory morbidity in people with SHS exposure but without spirometric chronic obstructive pulmonary disease, we examined a cohort of 256 subjects with prolonged occupational SHS exposure and preserved spirometry. We elicited symptom prevalence by structured questionnaires, examined functional capacity (maximum oxygen uptake, VO2max ) by exercise testing, and estimated associations of those outcomes with air trapping (plethysmography-measured residual volume-to-total lung capacity ratio, RV/TLC), and progressive air trapping with exertion (increase in fraction of tidal breathing that is flow limited on expiration during exercise (per cent of expiratory flow limitation, %EFL)). Results: RV/TLC was within the predicted normal limits, but was highly variable spanning 22%±13% and 16%±8% across the increments of FEV1 /FVC and FEV1, respectively. Respiratory complaints were prevalent (50.4%) with the most common symptom being ≥2 episodes of cough per year (44.5%). Higher RV/TLC was associated with higher OR of reporting respiratory symptoms (n=256; r 2 =0.03; p=0.011) and lower VO2max (n=179; r 2 =0.47; p=0.013), and %EFL was negatively associated with VO2max (n=32; r 2 =0.40; p=0.017). Conclusions: In those at risk for obstruction due to SHS exposure but with preserved spirometry, higher RV/TLC identifies a subgroup with increased respiratory symptoms and lower exercise capacity.